PENGARUH AKUNTABILITAS KEUANGAN, PENGAWASAN, DAN PENYAJIAN LAPORAN KEUANGAN TERHADAP PENGELOLAAN KEUANGAN DAERAH (Studi Pada Pemerintah Kota Dumai) - Muhammad Alqodri; Desmiyawati -; Pipin Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aims to examine at the effect of Financial Accountability, Control of Financial and Presentation of Financial Statements on Local Financial Management at the regional work units in the city of Dumai. Research carried out on 33 working units are located in city of Dumai 2014.Sampel that serve as the respondent proposive taken using the sampling method. Each population represented 2 respondents the head SKPD and technical head of the finance department. Questionnaires were distributed to 66 respondents, and successfully recovered the complete answer is obtained from 44 respondents. Data were collected from 44 respondents further data were analyzed with SPSS version 17.0 using descriptive statistical analysis and multiple linear regression analysis to produce the classic assumption test, model of data analysis, coefficient of determination and prove the hypothesis. Partial results of the study found that the variables of financial accountability and presentation of financial statements affect the financial management, while control variables did not affect the financial management. While testing and simultaneously discovered that the variables of financial accountability, financial control, and presentation of financial statements affect the financial management area.Keywords: Accountability, Control, Report, and Financial Management.